Impaired aldehyde dehydrogenase 1 subfamily member 2A-dependent retinoic acid signaling is related with a mesenchymal-like phenotype and an unfavorable prognosis of head and neck squamous cell carcinoma - Seidensaal, Katharina; Nollert, André; Feige, Agnes Hiou; Muller, Marie France; Fleming, Thomas; Gunkel, Nikolas; Plath, Karim; Grabe, Niels; Weichert, Wilko; Weber, Klaus-Josef; Plinkert, Peter K.; Simon, Christian; et al. (Molecular cancer, 2015)
An inverse correlation between expression of the aldehyde dehydrogenase 1 subfamily A2 (ALDH1A2) and gene promoter methylation has been identified as a common feature of oropharyngeal squamous cell carcinoma (OPSCC). Moreover, low ALDH1A2 expression was associated with an unfavorable prognosis of OPSCC patients, however the causal link between reduced ALDH1A2 function and treatment failure has not been addressed so far.
Gesehen am 15.06.020